Monitoring razvitiya sponsorstva rossiiskogo sporta - Kuzin, V. V.; Kutepov, M. E. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
To analyse the history of russian sport sponsorship's development was the purpose of this study. The discriptive-orientation approach was the method used in this research in cooperation with content-analysis used in the form of social monitoring. It had been concluded that the various forms of sport's supporting are using in contemporary Russia: sponsorship, patronage, charity etc. The main elements of sports sponsorship's organizational structure are the subjects (sponsors), objects (sponsored) and middlemen. The sponsorship in Russia had received the stable prioritized importance. The concrete objects of sponsorship help are first of all the sports competitions, clubs, teams, athletes, sports federations, physical culture-health improvement measures and mass festivals.